Major Molecular Signaling Pathways in Oral Cancer Associated With Therapeutic Resistance - Usman, Saima; Jamal, Ahmad; Teh, Muy-Teck; Waseem, Ahmad (Frontiers in Oral Health, 2021)
Oral cancer is a sub-category of head and neck cancers that initiates in the oral cavity. The primary treatment option for oral cancer remained surgery but it is associated with major disfigurement, inability to carryout normal oral functions, psycho-social stress and exhaustive rehabilitation. Chemotherapy is another treatment option that has limitations in terms of toxicity, intolerability, development of resistance to the chemical agents and non-specificity. Radiotherapy alone or in combination with other anticancer agents is also employed to treat the oral cancer but radiation by itself has the potential to cause cancer. The most common side effect of radiotherapy is the shaky nature of the radio beam at the point of entry causing needless exposure to the surrounding normal tissue. Another complication is the development of resistance and treatment failure. Immunological treatment to enhance body’s ability to recognise cancer tissue as a foreign entity are also being used but they are new and underdeveloped. Every treatment option has its own limitations. Although substantial achievements have been made in the treatment of oral cancer, this complex heterogeneous entity still require deeper knowledge of the role of key molecular players in carcinogenesis. More efforts should be focussed to dig out the molecular basis behind the development of resistance to therapeutic agents and how to combat it with the aim to improve the quality of life and survival of patient. In this review, an up-to-date overview is provided about the major factors contributing towards the development of therapeutic resistance in oral cancer along with the current ongoing strategies to overcome these challenges. The main focus of this review is to identify the genetic alterations and abrogated signalling pathways participating in the therapy resistance and treatment failure along with other factors such as tumour microenvironment and pharmacokinetic failures.